Effect Knowledge and Attitude with Behaviour of HPV Vaccination in Women of Reproductive Age: Pengaruh Pengetahuan dan Sikap dengan Perilaku Vaksinasi HPV pada Wanita Usia Reproduksi - Darmawan, Budi; Laihad, Bismarck J.; Wagey, Frank M. M. (Indonesian Journal of Obstetrics and Gynecology, 2023)
To observe the association between knowledgeand attitude towards HPV vaccination with the behaviortowards HPV vaccination on reproductive woman inIndonesia.Methods: We conducted observational analytic studywith cross-sectional design. The study was conducted inobstetric and gynecologic outpatient clinic in Prof. Dr. R.D. Kandou General Hospital, Manado Indonesia throughJuly and August 2021. Reproductively active woman wereincluded as the subject. Univariate and bivariate analysiswere conducted in this study.Results: We included 364 reproductive woman. The majorityof the subject were 20-35 year-old woman (50.8%) and weremarried (61.3%). The majority of the subject (72.8%) havereceived information about HPV vaccination. We foundsignificant association between knowledge and attitudewith the OR of 5.57 (p=0.00). Knowledge and attitudeshowed significant association with eagerness towards HPVvaccination. However, knowledge and behavior did notshow any significant association towards HPV vaccinationbehavior.Conclusion: There is a significant association betweenknowledge and attitude of HPV vaccination with eagernesstoward HPV vaccination in reproductive women in Indonesia.Keywords: behavior, HPV vaccination, knowledge,reproductive women. Keywords: behavior, HPV vaccination, knowledge,reproductive women. AbstrakTujuan: Untuk mengetahui hubungan pengetahuan dansikap terhadap perilaku vaksinasi HPV pada perempuan usiareproduktif di RSUP Prof. DR. R. D. Kandou, Manado.Metode: Penelitian ini merupakan penelitian analitikobservasional dengan pengambilan subjek potong lintang.Penelitian dilakukan di unit pelayanan bagian Obstetri danGinekologi RSUP Prof. Dr. R. D. Kandou Manado pada Juli-Agustus 2021. Subjek penelitian merupakan perempuanusia reproduktif yang bersedia untuk mengikuti penelitianini. Analisis data akan dilakukan secara univariat dan bivariatserta dilaporkan pada penelitian ini.Hasil: Penelitian ini mencakup 364 perempuan dengan usiaproduktif. Mayoritas subjek merupakan perempuan denganusia 20-35 tahun (50,8%) dan sudah menikah (61,3%).Mayoritas subjek (72,8%) pernah mendapatkan informasivaksinasi HPV sebelumnya. Hubungan antara pengetahuandan sikap terhadap vaksinasi menunjukkan hasil yangsignifikan (p=0,00) dengan OR 5,57. Pengetahuan dansikap juga menunjukkan hubungan yang signifikan dengankesediaan vaksin (p<0,05). Pengetahuan dan sikap tidakmenunjukkan hubungan yang bermakna terhadap perilakuvaksin (p>0,05).Kesimpulan: Terdapat hubungan yang bermakna antarapengetahuan dan sikap dengan perilaku keinginan vaksinasiHPV pada perempuan usia reproduktif.Kata kunci: pengetahuan, perempuan usia reproduktif,sikap, Vaksinasi HPV.